Relationship between religiosity and individual economic achievement: evidence from South Kalimantan, Indonesia = العلاقة بين التدين والإنجاز الاقتصادي للأفراد: ادلة من جنوب كاليمانتان, إندونسيا - Abdullah Yusof, Selamah; Budiman, Mohammad Arif; Mohd Amin, Ruzita (King Abdul Aziz University, 2018)
This study investigates the effect of religiosity on economic development or achievement of individuals in South Kalimantan, Indonesia. This province is of interest as its people are viewed as highly religious but lagging in economic development. The study attempts to address the measurement issues found in earlier studies at the micro level of analysis by constructing a multi-dimensional measure of religiosity. This study considers five dimensions of religion, namely: ritualistic, experiential, ideological, consequential and intellectual. Apart from the construction of a multi-dimensional measure of religiosity, an indicator of economic wellbeing is formulated other than income. The results show that Muslims in South Kalimantan have a high level of religiosity and that those with higher level of religiosity are economically better-off. Education was also found to be a significant determinant of individual economic achievement. Hence, religion and education must be emphasized for economic progress especially for South Kalimantan which has a low level of education.